ANALISIS GENDER DALAM KEHIDUPAN KELUARGA PEMBUDIDAYA RUMPUT LAUT (EUCHEUMA SP) DI KELURAHAN PANTAI AMAL KECAMATAN TARAKAN TIMUR - Nurlina -; Dayang Diah Fidhiani; Qoriah Saleha (2339-1324, 2020)
The purpose of this research is to examine how people's perceptions to gender roles in families, to describe the division of labor in productive, reproductive, and social activities, to examine how the opportunities of access and control that men and women, to examine how the opportunities of decision-making that men and women have in the seaweed cultivation business. The sample in this research amounted to 30 families of seaweed cultivators with the criteria of a married couple using a qualitative approach, which was obtained by interview using a questionnaire and direct observation data which obtained by analyzed descriptively. The result of this research indicate that: (1) Perceptions of gender that are most highly held by both men and women are